Metagenomics profiling for assessing microbial diversity in both active and closed landfills - Zainun, Mohamad Yusof; Simarani, Khanom (Elsevier, 2018)
The municipal landfill is an example of human-made environment that harbours some complex diversity of microorganism communities. To evaluate this complexity, the structures of bacterial communities in active (operational) and closed (non-operational) landfills in Malaysia were analysed with culture independent metagenomics approaches. Several points of soil samples were collected from 0 to 20 cm depth and were subjected to physicochemical test, such as temperature, pH, and moisture content. In addition, the heavy metal contamination was determined by using ICPMS. The bacterial enumeration was examined on nutrient agar (NA) plates aerobically at 30 °C. The soil DNA was extracted, purified and amplified prior to sequence the 16S rRNA gene for statistical and bioinformatics analyses. As a result, the average of bacteria for the closed landfill was higher compared to that for the active landfill at 9.16 × 107 and 1.50 × 107, respectively. The higher bacterial OTUs sequenced was also recorded in closed landfills compared to active landfill i.e. 6625 and 4552 OTUs respectively. The data from both landfills showed that the predominant phyla belonged to Proteobacteria (55.7%). On average, Bacteroidetes was the second highest phylum followed by Firmicutes for the active landfill. While the phyla for communities in closed landfill were dominated by phyla from Acidobacteria and Actinobacteria. There was also Euryarchaeota (Archaea) which became a minor phylum that was detected in active landfill, but almost completely absent in closed landfill. As such, the composition of bacterial communities suggests some variances between the bacterial communities found in active and closed landfills. Thus, this study offers new clues pertaining to bacterial diversity pattern between the varied types of landfills studied.